Flexibility in the Receptor-Binding Domain of the Enzymatic Colicin E9 Is Required for Toxicity against Escherichia coli Cells - Penfold, Christopher N. (American Society for Microbiology, 2004)
The events that occur after the binding of the enzymatic E colicins to Escherichia coli BtuB receptors that lead to translocation of the cytotoxic domain into the periplasmic space and, ultimately, cell killing are poorly understood. It has been suggested that unfolding of the coiled-coil BtuB receptor binding domain of the E colicins may be an essential step that leads to the loss of immunity protein from the colicin and immunity protein complex and then triggers the events of translocation. We introduced pairs of cysteine mutations into the receptor binding domain of colicin E9 (ColE9) that resulted in the formation of a disulfide bond located near the middle or the top of the R domain. After dithiothreitol reduction, the ColE9 protein with the mutations L359C and F412C (ColE9 L359C-F412C) and the ColE9 protein with the mutations Y324C and L447C (ColE9 Y324C-L447C) were slightly less active than equivalent concentrations of ColE9. On oxidation with diamide, no significant biological activity was seen with the ColE9 L359C-F412C and the ColE9 Y324C-L447C mutant proteins; however diamide had no effect on the activity of ColE9. The presence of a disulfide bond was confirmed in both of the oxidized, mutant proteins by matrix-assisted laser desorption ionization-time of flight mass spectrometry. The loss of biological activity of the disulfide-containing mutant proteins was not due to an indirect effect on the properties of the translocation or DNase domains of the mutant colicins. The data are consistent with a requirement for the flexibility of the coiled-coil R domain after binding to BtuB.